Hubungan Filsafat Pendidikan dengan Pembentukan Karakter Peserta Didik - Fanny Oktavia Anggraeni; Shobrun Jamil; Mochammad Rafli Hidayat; Maftukhatul Khoiriyah (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The family is the primary and fundamental educational environment in shaping individual morality and character. However, various family problems in modern society indicate a decline in moral values within family relationships. Therefore, examining the concept of family ethics from an Islamic perspective is essential to reaffirm normative guidance derived from the Qur’an and Hadith. This study aims to analyze the concept of moral values within the family based on the Qur’an and Hadith, focusing on ethics toward parents, marital relationships, and kinship ties. This research employs a qualitative approach using library research methods. Data were collected from relevant Qur’anic verses, Prophetic traditions, and supporting literature such as Qur’anic exegesis, hadith commentaries, and scholarly works related to Islamic ethics and family studies. Data analysis was conducted using a descriptive-analytical method. The findings reveal that Islamic family ethics emphasize filial piety (birr al-wālidain) as a fundamental obligation with high spiritual significance, marital relations based on mutual rights and responsibilities grounded in the principles of sakinah, mawaddah, and rahmah, and kinship relations as an expression of piety through maintaining social ties and mutual care. These findings indicate that the comprehensive implementation of Islamic family ethics plays a vital role in fostering harmonious families and contributing to the development of a moral and civilized society.